2020
DOI: 10.3389/fpsyg.2020.571101
|View full text |Cite
|
Sign up to set email alerts
|

Current and Retrospective Childhood Ratings of Emotional Fluctuations in Adults With ADHD

Abstract: Introduction: Emotional fluctuations and mood swings are common among adults with Attention Deficit/Hyperactivity Disorder (ADHD). Here we investigated if these problems could be retrospectively traced back to childhood behavior.Methods: Adults with an ADHD diagnosis (n = 502, 48% female) and a population-based control sample (n = 818, 59% female) completed the Adult ADHD Self-report Scale (ASRS), the Wender Utah Rating Scale (WURS) and the Mood Disorder Questionnaire (MDQ). All participants also provided self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 52 publications
(70 reference statements)
2
9
2
Order By: Relevance
“…Mowlem et al (2019) found that females with ADHD had higher levels of emotional lability than males with ADHD, although this difference was not statistically significant. In contrast to most other findings related to sex and gender, Lundervold et al (2020) found that males were more likely to be in the group with emotional fluctuations.…”
Section: Demographic Factorscontrasting
confidence: 99%
See 4 more Smart Citations
“…Mowlem et al (2019) found that females with ADHD had higher levels of emotional lability than males with ADHD, although this difference was not statistically significant. In contrast to most other findings related to sex and gender, Lundervold et al (2020) found that males were more likely to be in the group with emotional fluctuations.…”
Section: Demographic Factorscontrasting
confidence: 99%
“…Further, they found that emotional dysregulation was more strongly related to hyperactive and impulsive symptoms than inattentive symptoms. This finding is consistent with Lundervold et al's (2020) findings that hyperactive/impulsive symptoms were stronger predictors of mood fluctuations than inattentive symptoms.…”
Section: Psychological Factorssupporting
confidence: 92%
See 3 more Smart Citations